2022
DOI: 10.3390/polym14142813
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Modification of Spruce and Maple Wood for Special Wood Products

Abstract: This article presents a proposal of thermal modification of Norway spruce and sycamore maple for special wood products, mainly for musical instruments. Selected physical and acoustical characteristics (PACHs), including the density (ρ), dynamic modulus of elasticity along the wood grain (EL), specific modulus (Esp), speed of sound along the wood grain (cL), resonant frequency (fr) and acoustic constant (A), logarithmic decrement (ϑ), loss coefficient (η), acoustic conversion efficiency (ACE), sound quality fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
7
0
4
Order By: Relevance
“…The principle of the ultrasound (US) measurements is presented in Figure 4 [ 17 ]. The density of each plate was also determined in each stage of the experiment, and the longitudinal and radial modulus of elasticity was calculated in accordance with the calculation relationship mentioned by [ 26 ]. The mean (MV) and standard deviation (SD) values of the measured parameters were recorded before and during exposure to temperature and UV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of the ultrasound (US) measurements is presented in Figure 4 [ 17 ]. The density of each plate was also determined in each stage of the experiment, and the longitudinal and radial modulus of elasticity was calculated in accordance with the calculation relationship mentioned by [ 26 ]. The mean (MV) and standard deviation (SD) values of the measured parameters were recorded before and during exposure to temperature and UV.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have addressed the problem of the photodegradation of wooden surfaces due to UV and thermal radiation, but very few of them have analyzed the acoustic and physical changes produced in the resonance wood used for musical instruments [ 17 , 23 , 24 , 25 , 26 , 27 ]. Noguch et al 2012 [ 17 ] and Obataya 2017 [ 24 ] observed an increase in the stiffness of naturally aged wood by approximately 38% in 121-year-old wood, after which a decrease was observed with increasing aging time.…”
Section: Introductionmentioning
confidence: 99%
“…A eficiência da conversão acústica (ECA) está diretamente associada à eficiência da conversão da energia de vibração do material em energia acústica. Essa grandeza é útil para mostrar os efeitos de grupo, por exemplo, o efeito da radiação acústica e da atenuação acústica juntos [12,23]. A ECA comumente associa a razão entre o coeficiente de radiação acústica pela atenuação acústica apresentada pelo material da amostra (Equação 5).…”
Section: Ensaio De Vibração Transversalunclassified
“…Resultados semelhantes foram relatados por DANIHELOVÁ et al [23] que submeteram madeiras de Picea abies (L.) Karst. e Acer pseudoplatanus, L. a processos térmicos utilizando a técnica ThermoWood ® e tratamentos a 135, 160 e 185 °C.…”
Section: Módulo De Elasticidade Dinâmico Específico (E Esp )unclassified
“…The desire of musical instrument manufacturers to reduce the negative characteristics of raw material wood through special modification processes has existed for a century now [ 43 , 44 ]. In research by Danihelova et al [ 45 ], the authors investigated the suitability of thermally modified (ThermoWood process) Norway spruce and sycamore maple for special wood products, mainly for musical instruments. Selected physical and acoustical characteristics (PACHs) including density, dynamic modulus of elasticity along the wood grain, specific modulus, speed of sound along the wood grain, resonant frequency, acoustic constant, logarithmic decrement, loss coefficient, acoustic conversion efficiency, sound quality factor and the timbre of sound were evaluated.…”
mentioning
confidence: 99%